WDR8 is a centriolar satellite and centriole-associated protein that promotes ciliary vesicle docking during ciliogenesis - Kurtulmus, Bahtiyar; Wang, Wen-bo; Ruppert, Thomas; Neuner, Annett; Cerikan, Berati; Viol, Linda; Gruss, Oliver; Pereira, Gislene (Journal of cell science, 2015)
Ciliogenesis initiates at the mother centriole through a series of events that include membrane docking, displacement of cilia-inhibitory proteins and axoneme elongation. Centriolar proteins, in particular at distal and subdistal appendages, carry out these functions. Recently, cytoplasmic complexes named centriolar satellites have also been shown to promote ciliogenesis. Little is known about the functional and molecular relationship between appendage proteins, satellites and cilia biogenesis. Here, we identified the WD-repeat protein 8 (WDR8, also known as WRAP73) as a satellite and centriolar component. We show that WDR8 interacts with the satellite proteins SSX2IP and PCM1 as well as the centriolar proximal end component Cep135. Cep135 is required for the recruitment of WDR8 to centrioles. Depletion experiments revealed that WDR8 and Cep135 have strongly overlapping functions in ciliogenesis. Both are indispensable for ciliary vesicle docking to the mother centriole and for unlocking the distal end of the mother centriole from the ciliary inhibitory complex CP110-Cep97. Our data thus point to an important function of centriolar proximal end proteins in ciliary membrane biogenesis, and establish WDR8 and Cep135 as two factors that are essential for the initial steps of ciliation.